THE MAN'S FRAGILITY OF THE MALE MAIN CHARACTER IN THE BARBIE MOVIE (2023) - David, Deva Putri; Mustikawati, Yunitari; Nurfadhilah, Auliyanti Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study offers a valuable contribution to the intersection of psychology and literature, as well as provides insights for the general public regarding the portrayal of male fragility and its underlying causes. The purpose of this research is to analyze how male fragility is reflected in the main male character, “Ken,” and to examine the reasons behind the emergence of this fragility in the Barbie film by Greta Gerwig and Noah Baumbach (2023). The analysis employs critical discourse analysis based on Fairclough’s (2013) framework to explore the complex interplay between power relations and societal norms conveyed through cinematic elements, focusing particularly on the character of Ken. A qualitative descriptive method is used to interpret these findings. The study reveals that Ryan Gosling’s character demonstrates various forms of masculine fragility, including emotional expressiveness, physical inadequacy, intellectual inferiority, subordination to women, failure to fulfill masculine expectations in work-related contexts, and sexual inadequacy. The research also identifies several causes of Ken’s fragility, namely rigid masculine norms, identity discrepancies, conformity pressures, societal expectations, and cultural norms. These findings lead to the conclusion that the Barbie movie (2023) not only presents a critique of patriarchy but also highlights the negative impacts of masculinity norms on men who become trapped within societal expectations. The male fragility portrayed through Ken reflects a widely relevant gender issue, in which men often experience emotional vulnerability due to social and cultural pressures to conform to restrictive masculine ideals.